Managing project-to-project and project-to-organization interfaces in programs: Organizational integration in a global operations expansion program. Issue 4 (May 2015) - Turkulainen, Virpi; Ruuska, Inkeri; Brady, Tim; Artto, Karlos
Abstract: Managing project-to-project and project-to-organization interfaces is a critical part of program management. However, previous program management research says little about management of these two important interfaces. We study a global operations expansion program at Neste Oil when it expanded its renewable fuels operations globally with four plant projects in 2005–2011, examining how integration is managed in project-to-project and project-to-organization interfaces. Our analysis provides understanding on how management of organizational integration is contingent on the interface by illustrating use of different types of integration mechanisms in those two interfaces. The findings are novel in the context of program management, and the theoretical contributions focus on research on program management especially from an organizational integration and contingency analysis perspective. Highlights: We address how organizational integration is managed in a program across project-to-project and project-to-organization interfaces. Our empirical context is a global operations expansion program. Our data is from Neste Oil when it expanded its renewable fuels operations globally with four projects in 2005–2011. We provide illustrations on the use of integration mechanisms in project-to-project and project-to-organization interfaces. Our analysis provides understanding on how management of organizational integration is contingent on the interface.